The Berenstain bears down on the farm. - Berenstain, Stan 1923- (New York : HarperCollins, 2006)
The berenstain bears visit farmer and Mre. Ben's farm and learn about their life there.
"1, beginning reading."
Keywords: Farm life -- Juvenile fiction; Bears -- Juvenile fiction